Contemporary developments in high-frequency photonic devices - Bhattacharyya, Siddhartha 1975-; Debnath, Pampa; Deyasi, Arpan; Dey, Nilanjan 1984- (IGI Global, 2019)
"This book examines a wider aspect of microwave engineering and photonic technology and its applications. It also focuses on the developments of devices/structures with different materials and have different optical properties"--